Associations of Unscavenged Anesthetic Gases and Long Working Hours With Preterm Delivery in Female Veterinarians - Shirangi, A.; Fritschi, Lin; Holman, C D. (Lippincott Williams & Wilkins, 2009)
OBJECTIVE: To examine whether occupational hazards such as anesthetic gases, radiation, pesticides, and working hours in veterinary practice are associated with preterm delivery (before 37 weeks of gestation) in female veterinarians. METHODS: The Health Risks of Australian Veterinarians project was conducted as a questionnaire-based survey of all graduates of Australian veterinary schools during the 40-year period 1960–2000. Approximately 1,200 female veterinarians participated in the survey. Pregnancy was defined as the unit of analysis. We restricted analyses to pregnancies of those women who reported being employed when the pregnancy began and were working only in clinical practice. Of 1,355 pregnancies in total in the file, 744 pregnancies were eligible for the final analysis. RESULTS: The prevalence of preterm birth in women exposed to unscavenged anesthetic gases was 7.3% compared with 5.7% in the general population. In a Cox proportional hazards model controlling for the potential confounders, there was a significant 2.5-fold increase (hazard ratio 2.56, 95% confidence interval [CI] 1.33–4.91) in the risk of preterm delivery in women exposed to unscavenged anesthetic gases for 1 or more hours per week compared with the unexposed group (women who did not perform surgery and those who performed surgery in the presence of a scavenger system). A dose–response relation also was found within this group when exposure was divided into finer categories. There was also a strong and monotonic increase in risk of preterm delivery and the number of hours worked per week with veterinarians working more than 45 hours a week (hazard ratio 3.69, 95% CI 1.40–9.72) compared with those working fewer than 45 hours per week. CONCLUSION: Long working hours and performing surgery in the absence of a scavenger system for anesthetic gases are important risk factors for preterm birth in female veterinarians.